Sir John Soane and the Design of the New State Paper Office, 1829-1834 - Palmer, Susan (Archivaria, 2006)
This paper examines the design and building of the New State Paper Office in Duke Street, London by the architect Sir John Soane (1753–1837), the only purpose-built repository for national records in England before Sir James Pennethorne’s Public Record Office Building opened in Chancery Lane in 1856. It draws on published accounts, material in the Office of Works, and Treasury papers in The National Archives, and on Sir John Soane’s extensive business archive and office drawings preserved in his House-Museum, which he left to the nation on his death in 1837. Soane’s design for the building is examined particularly in respect to his solutions for fire-proofing and security, and compared with contemporary practice and the solutions adopted in the Public Record Office building of twenty years later. The final section deals with the building in use from 1834, its amalgamation with the Public Record Office in 1854, and its demolition in 1862. RÉSUMÉ Cet article se penche sur le design et la construction du New State Paper Office sur la rue Duke à Londres. Conçu par 1’architecte Sir John Soane (1753–1837), cet édifice est le seul bâtiment construit pour servir de dépôt d’archives en Angleterre, avant que le Public Record Office de Sir James Pennethorne se soit ouvert sur Chancery Lane en 1856. L’auteure se base sur les publications, les documents du ministère des Travaux publics et des Finances aux Archives nationales, ainsi que sur les archives d’entreprise considérables et les dessins de Sir John Soane laissés après sa mort en 1837 et conservés dans son musée. Le design de Soane pour cet édifice est examiné particulièrement du point de vue de la protection du feu et de la sécurité, et est aussi comparé aux pratiques contemporaines et aux solutions adoptées pour la construction du Public Record Office vingt ans plus tard. Dans une dernière partie, 1’auteure aborde 1’édifice tel qu’il a été utilisé après 1834, sa fusion avec le Public Record Office en 1854 et sa démolition en 1862.